Structure of the Ecuadorian forearc from the joint inversion of receiver functions and ambient noise surface waves. Issue 3 (15th May 2020) - Koch, Clinton D; Lynner, Colton; Delph, Jonathan; Beck, Susan L; Meltzer, Anne; Font, Yvonne; Soto-Cordero, Lillian; Hoskins, Mariah; Stachnik, Josh C; Ruiz, Mario; Alvarado, Alexandra; Agurto-Detzel, Hans; et al.
SUMMARY: The Ecuadorian forearc is a complex region of accreted terranes with a history of large megathrust earthquakes. Most recently, a M w 7.8 megathrust earthquake ruptured the plate boundary offshore of Pedernales, Ecuador on 16 April 2016. Following this event, an international collaboration arranged by the Instituto Geofisico at the Escuela Politécnica Nacional mobilized a rapid deployment of 65 seismic instruments along the Ecuadorian forearc. We combine this new seismic data set with 14 permanent stations from the Ecuadorian national network to better understand how variations in crustal structure relate to regional seismic hazards along the margin. Here, we present receiver function adaptive common conversion point stacks and a shear velocity model derived from the joint inversion of receiver functions and surface wave dispersion data obtained through ambient noise cross-correlations for the upper 50 km of the forearc. Beneath the forearc crust, we observe an eastward dipping slow velocity anomaly we interpret as subducting oceanic crust, which shallows near the projected centre of the subducting Carnegie Ridge. We also observe a strong shallow positive conversion in the Ecuadorian forearc near the Borbon Basin indicating a major discontinuity at a depth of ∼7 km. This conversion is not ubiquitous and may be the top of the accreted terranes. We also observe significant north–south changes in shear wave velocity. The velocity changes indicate variations in the accreted terranes and may indicate an increased amount of hydration beneath the Manabí Basin. This change in structure also correlates geographically with the southern rupture limit of multiple high magnitude megathrust earthquakes. The earthquake record along the Ecuadorian trench shows that no event with a M w >7.4 has ruptured south of ∼0.5°S in southern Ecuador or northern Peru. Our observations, along with previous studies, suggest that variations in the forearc crustal structure and subducting oceanic crust may influance the occurrence and spatial distribution of high magnitude seismicity in the region.